Emerging Technologies for Rapid Identification of Bloodstream Pathogens. (24th April 2014) - Kothari, Atul; Morgan, Margie; Haake, David A.
Abstract : Technologies for rapid microbial identification are poised to revolutionize clinical microbiology and enable informed decision making for patients with bloodstream infections. When combined with antibiotic stewardship programs, these approaches have been shown to improve clinical outcomes and reduce healthcare expenditures. Abstract : Technologies for rapid microbial identification are poised to revolutionize clinical microbiology and enable informed decision making for patients with life-threatening bloodstream infections. Species identification of microorganisms in positive blood cultures can be performed in minutes using commercial fluorescence in situ hybridization tests or mass spectroscopy. Microorganisms in positive blood cultures can also be identified within 1–2.5 hours using automated polymerase chain reaction–based systems that can also detect selected antibiotic resistance markers, such as methicillin resistance. When combined with antibiotic stewardship programs, these approaches improve clinical outcomes and reduce healthcare expenditures. Tests for direct detection in whole blood samples are highly desirable because of their potential to identify bloodstream pathogens without waiting 1-2 days for blood cultures to become positive. However, results for pathogen detection in whole blood do not overlap with those of conventional blood culture techniques and we are still learning how best to use these approaches.